Ethnic diversity management in France: a multilevel perspective. Issue 1 (11th January 2019) - Hennekam, Sophie; Bacouel-Jentjens, Sabine; Yang, Inju
Abstract : Purpose: The purpose of this paper is to present a case study of the multilevel factors that influence the way in which an organization approaches ethnic diversity management in France. Syed and Özbilgin's (2009) relational framework was adopted to understand and contextualize ethnic diversity management in a car manufacturing company in France. Design/methodology/approach: In total, 37 semi-structured in-depth interviews with employees of different hierarchical levels in a French organization have been conducted and analyzed using the Gioia method. Findings: The findings show that the lack of clear laws and the universal citizenship model on macro-level coupled with the gendered industry and superficial engagement with ethnic diversity on meso-level overlooks the difficult situation of ethnic minorities in the workplace, especially women. However, the findings also stress that it is on individual level that resilience and agency can be expressed, which means that despite the perceived barriers on societal and organizational level, ethnic minorities are motivated to improve the way they are treated in organizations. Originality/value: Ethnic minorities are an understudied dimension of diversity management in organizations. The findings underscore the importance of the intersection of ethnicity and gender as this affects the career development possibilities and daily work experience of ethnic minority women.